PCR detection of Vibrio cholerae, Escherichia coli, and Salmonella sp. from bottled drinking water in Iran - Mojtaba Bonyadian; Hamdallah Moshtaghi; Hanie Nadi (Journal of Infection in Developing Countries)
Introduction: The quality of drinking water has an important role in human health. This study was aimed to detect Escherichia. coli, Salmonella sp. and Vibrio cholerae from bottled drinking waters produced in Iran.